2006
DOI: 10.2527/2006.8411
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prenatal muscle tissue expression profiles of two pig breeds differing in muscle characteristics1

Abstract: The objective of this study was to compare purebred Duroc and Pietrain prenatal muscle tissue transcriptome expression levels at different stages of prenatal development to gain insight into the differences in muscle tissue development in these pig breeds. Commercial western pig breeds have been selected for muscle growth for the past 2 decades. Pig breeds differ for their muscle phenotypes (i.e., myofiber numbers and myofiber types). Duroc and Pietrain pig breeds are extremes; Duroc pigs have redder muscle fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 27 publications
12
88
0
Order By: Relevance
“…We studied the transcriptome expression in porcine longissimus dorsi muscles of Duroc pigs. The results showed that especially the primary wave of prenatal muscle fibre formation is strongly genetically regulated, while the secondary muscle fibre formation is associated with much less differential gene expression (te Pas et al, 2005;Cagnazzo et al, 2006). This is in agreement with the fact that the secondary muscle fibre formation can be regulated with feed, while the primary muscle fibre formation cannot be affected Stickland et al, 2004;reviewed in Rehfeldt et al, 2011a, b).…”
Section: Prenatal Muscle Tissue Development Related To Post-mortem Mesupporting
confidence: 76%
See 1 more Smart Citation
“…We studied the transcriptome expression in porcine longissimus dorsi muscles of Duroc pigs. The results showed that especially the primary wave of prenatal muscle fibre formation is strongly genetically regulated, while the secondary muscle fibre formation is associated with much less differential gene expression (te Pas et al, 2005;Cagnazzo et al, 2006). This is in agreement with the fact that the secondary muscle fibre formation can be regulated with feed, while the primary muscle fibre formation cannot be affected Stickland et al, 2004;reviewed in Rehfeldt et al, 2011a, b).…”
Section: Prenatal Muscle Tissue Development Related To Post-mortem Mesupporting
confidence: 76%
“…These findings suggest that the primary myogenesis process is more intense in Duroc than in Pietrain embryos but that the secondary myogenesis that occurs later during gestation is more intense in Pietrain foetuses than in Duroc foetuses (Cagnazzo et al, 2006). These results were confirmed by Davoli et al (2011) using PCR tests.…”
Section: Prenatal Muscle Tissue Development Related To Post-mortem Mesupporting
confidence: 76%
“…23 . Here, we reported the mRNA expression of three MRFs, two paired box and two bone morphogenetic protein gene.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to characterise the histological phenotype of the tissue alongside the gene expression phenotype will go some way towards addressing these issues. Notwithstanding these limitations, gene and protein expression profiling approaches have been directed at muscle of cattle (Table 4) and other livestock species, such as the pig (Lin and Hsu, 2005;Plastow et al, 2005;Cagnazzo et al, 2006). Some recent insights into bovine muscle biology that have been obtained by cattle muscle profiling are described, as follows.…”
Section: Applications Of Functional Genomicsmentioning
confidence: 99%